Management Learning Based on Character Education in Elementary Schools - Handayani, Neti (Yayasan Sembilan Pemuda Indonesia, 2023)
Study This aim for analyzing management learning-based education character at school. This was implemented in SD Negeri 1 Jejawi. Method used is method qualitative. Data collection tool using method interview, documentation, observation as well as study library. Data analysis using qualitative descriptive analysis with stages gathering data, data reduction, data presentation, with draw conclusion. Research results state that planning learning drip focus on improvement matched performance with development character students. Implementation learning more prioritize on aspects formation character-based learning practice than theory in order students active during the learning process and can apply values character in activity learning, doing characteristic approach habituation to Shiva from approach with penalties and sanctions. Evaluation focuses on achievement or success implementation learning. Achievement implementation learning based character rated in a manner comprehensive based on aspect affective, cognitive as well as psychomotor student.